Dancing to "groovy" music enhances the experience of flow. Issue 1 (6th May 2018) - Bernardi, Nicolò F.; Bellemare‐Pepin, Antoine; Peretz, Isabelle
Abstract: We investigated whether dancing influences the emotional response to music, compared to when music is listened to in the absence of movement. Forty participants without previous dance training listened to "groovy" and "nongroovy" music excerpts while either dancing or refraining from movement. Participants were also tested while imitating their own dance movements, but in the absence of music as a control condition. Emotion ratings and ratings of flow were collected following each condition. Dance movements were recorded using motion capture. We found that the state of flow was increased specifically during spontaneous dance to groovy excerpts, compared with both still listening and motor imitation. Emotions in the realms of vitality (such as joy and power) and sublimity (such as wonder and nostalgia) were evoked by music in general, whether participants moved or not. Significant correlations were found between the emotional and flow responses to music and whole‐body acceleration profiles. Thus, the results highlight a distinct state of flow when dancing, which may be of use to promote well‐being and to address certain clinical conditions. Abstract : We investigated whether dancing influences the emotional response to music, compared to when music is listened to in the absence of movement. We found that the state of flow was increased specifically during spontaneous dance to groovy excerpts, which may be of use to promote well‐being and to address certain clinical conditions.